Anaisis Resiko Penjualan, Perputaran Piutang Terhadap Profitabilitas Perusahaan - Supriadi, Yoyon; Yuridhiska, Ghesti (Jurnal Ilmiah Manajemen Kesatuan, 2015)
The purpose of this study is to determine the effect of the risk of sales, accounts receivable turnover to the company's profitability. case studies on PT.Tiga Pilar Sejahtera Tbk, PT.Mayora Indah Tbk, and Aneka Niaga Tbk PT.Prasidha. To determine how much influence the risk of sales, accounts receivable turnover to the company profitabilias PT.Tiga Pilar Sejahtera Tbk, PT.Mayora Indah Tbk, and PT.Prasidha Aneka Niaga Tbk. The results showed that PT.Tiga Pilar Sejahtera Tbk, PT.Mayora Indah Tbk, and PT.Prasidha Aneka Niaga Tbk has a value of R Square of 0.313 or 31.3% of sales and that means risk variables were able to explain the variable accounts receivable turnover of 0,313 corporate profitability or 31.3%. While the remaining 0.687 or 68.7% is influenced by other factors. Evaluation results of this study indicate that PT.Tiga Pilar Sejahtera Tbk, PT.Mayora Indah Tbk, and PT.Prasidha Aneka Niaga Tbk are expected to be more effective in managing their receivables turnover to increase sale, thus profits generate will have more leverage and profitability can be increased. Keywords: Risk Sales, Accounts Receivable Turnover, Profitability